Finely tuned fiber-based porous structures for bone tissue engineering applications - Ribeiro, Viviana Pinto (2016)
[Excerpt] Scaffolds developed for bone tissue engineering (TE) must possess specific structural properties to allow neo-tissue formation and integration within the material[1]. Several polymeric systems and processing methodologies have been proposed to develop bone TE scaffolds. Nevertheless, the so far proposed strategies do not fulfil all the requirements for effective bone regeneration. Textile technologies have recently emerged as an industrial route for producing more complex fibre-based porous scaffolds[2]. Silk fibroin (SF) from Bombyx mori has already proved to be a good biomaterial for bone TE[3]. SF-based structures are known for the impressive mechanical properties and biocompatibility, which meet the basic requirements for developing bone TE scaffolds[4],[5]. [...]